KEBIJAKAN PEMERINTAH KECAMATAN PUJON DALAM MENANGGULANGI TANAH LONGSOR DI DUSUN KEDUNGREJO - Nofindy Citra Danisma; Amanda Ayu Febriana; Hayat, Hayat (Jurnal Cakrawala Ilmiah, 2024)
Landslides are a natural phenomenon in the form of movement of land masses in search of a new balance due to external disturbances which cause a reduction in soil shear strength and an increase in soil shear stress. The main factors that influence the occurrence of landslides include rainfall, soil type, land use and slope slope. The aim of this research is to find out how the Pujon sub-district government handles landslides and identify factors influencing landslides. This research was carried out using a literature review research method which provides output on existing data, as well as an explanation of a discovery so that it can be used as an example for research studies in compiling or making a clear discussion of the content of the problem to be researched. The author looks for data or literary material from journals or articles and also references from books so that it can be used as a strong basis for the content or discussion.